Cross-Layer Mechanism for Efficient Video Transmission over Mobile Ad Hoc Networks - Christos Bouras; Vaggelis Kapoulas; Apostolos Gkamas; G Kioumourtzis; George Adam; Nikos Tavoularis (The Third International Workshop on Cross Layer Design, Rennes, France, 2011)
Abstract- Mobile ad hoc networks (MANETs) are becoming more essential to wireless communications due to growing popularity of mobile devices. However, MANETs do not seem to effectively support multimedia applications and especially video transmission. This paper presents a cross-layer mechanism for efficient video transmission over this type of networks. The proposed mechanism consists of a priority-scheduling algorithm, at the network layer, and the use of the IEEE 802.11e standard at the MAC layer. The priority-scheduling algorithm takes into account the frame type of the MPEG-4 video file in order to provide different priorities to the most important video packets. At the MAC layer, the IEEE 802.11e protocol assigns the highest priority to video applications to reduce delay and packets losses due to other competing traffic. This design is easily implemented in any ad hoc wireless network as an extension on the AODV MANET routing protocol. Simulation results conducted with the network simulator ns-2 show the advantages of the proposed design.